2017
DOI: 10.3354/esr00788
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach for assessing translocation as an effective conservation tool for Hawaiian monk seals

Abstract: For threatened and endangered species, translocations have been widely used to mitigate multiple sources of mortality that threaten population recovery. Although numerous Hawaiian monk seals Neomonachus schauinslandi have been translocated for a variety of purposes, few monk seal translocations have addressed the problem of prey limitation. To assess the efficacy of using translocations to mitigate reduced prey availability, 12 weanling monk seals were translocated with pre-release health screening and post-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Short-term ex situ methods, without captive propagation, have been applied to other marine mammals, with the translocation and/or release of individuals temporarily removed from the wild. For example, human intervention has led to increased survival of endangered Hawaiian monk seals Neomonachus schauinslandi, with as much as a third of the population benefitting from such efforts (Harting et al 2014, Norris et al 2017. One major challenge with implementing an ex situ approach with the vaquita is that experience with releasing cetaceans from human care is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term ex situ methods, without captive propagation, have been applied to other marine mammals, with the translocation and/or release of individuals temporarily removed from the wild. For example, human intervention has led to increased survival of endangered Hawaiian monk seals Neomonachus schauinslandi, with as much as a third of the population benefitting from such efforts (Harting et al 2014, Norris et al 2017. One major challenge with implementing an ex situ approach with the vaquita is that experience with releasing cetaceans from human care is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic translocations have been implemented for a number of carnivores in the United States (Wisely et al ) and Europe (SimĂłn et al ). Such repeated translocations can increase survivorship (Norris et al ) and the number of reproductive adults (Marino et al ), and enhance short‐term population growth (Kinley and Newhouse ). However, such benefits are not guaranteed, and some translocations fail to enhance reproductive output (Manlick et al ) or population size (Hayward et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Faced with this grim situation, an experiment was conducted to evaluate whether conservation translocations from a subpopulation with low juvenile survival to a site where survival prospects were likely better might be an effective tool to mitigate early mortality. Thus, in 2008Thus, in -2009, a total of 12 weaned pups was removed from French Frigate Shoals (where juvenile survival was especially poor) and released at Nihoa Island at the eastern end of the NWHI (Norris et al, 2017). Nihoa was chosen as the destination for the translocation experiment because recent increasing trends in index counts of seals at this site suggested that juvenile survival was likely favorable (Harting, Baker & Johanos, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nihoa was chosen as the destination for the translocation experiment because recent increasing trends in index counts of seals at this site suggested that juvenile survival was likely favorable (Harting, Baker & Johanos, 2017). Norris et al (2017) compared translocated and resident Nihoa Island seals' clinical health status, disease exposure, foraging behavior and habitat use. However, results regarding post-release survival of translocatees relative to seals remaining at French Frigate Shoals and residents at Nihoa were inconclusive for two reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation